(untitled) (Eurasian Journal of Philology Science and Education, 2016)
The reflection of the processes of categorization and changes of category by term in language in computer science from the perspective of cognitive of terminology is considered in the article. Analysis of the term category of process, the category of (virtual) objects, categories of attribute, the category of quantity, category of units, category of Science, sectors, categories of organizations and categories of profession based on the method of formal logic. Categorization process shown by the example of the definition of terms. Changes of category by term are illustrated by metonymic models of the term category of process.